Handbook of fractures 2026-02-15T14:53:30+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from session cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Egol, Kenneth A.; Koval, Kenneth J.; Zuckerman, Joseph D. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2010)

(untitled)
Intended for residents and practitioners seeking facts on fracture management and classification, this pocket-sized guide includes chapters organised by anatomic site providing key information on fractures in adults and in children, including epidemiology, anatomy, mechanism of injury, clinical evaluation, and more